Transcestrality, Travestiland, Traviarchy:: the stage and gender dissidences in Brazil - Meneses, Emerson (Revista Brasileira de Estudos da Presença, 2024)
Transcestrality, Travestiland, Traviarchy: the stage and gender dissidences in Brazil – This article aims to put into historical perspective the relationship between the arts (especially performing arts) and travestilities in Brazil since the beginning of the 20th century. Based on a literature review that included both academic works and non-academic documents, the study identifies three patterns (or paradigms) experienced by travesti artists in what refers to their insertion in society: transcestrality, travestiland, and, more recently, traviarchy. This allows a better interpretation and understanding of the role played by the current generation of these artists: if on the one hand they fuel social change with a work which is both artistic and political, on the other this role can only be understood as the result of a historical process, in which the importance and contribution of artists from the other two paradigms must be also recognized.